Pelatihan Pembuatan Mie Keke Superfood Sebagai Produk Unggulan Di Desa Tumuk Manggis Kabupaten Sambas - Muslimah, Muslimah; Kristiandi, Kiki; Trisnawati, Hikmah; Merdekawati, Dewi; Mahyudi, Indra; Ningsih, Irma Fahrizal Butsi (Pakis Journal Institute, 2025)
This community service activity was carried out in Tumuk Manggis Village, Sambas Regency, from September to October 2024, with the aim of introducing a new superfood-based food product, namely keke noodles, as the village's superior product. This product utilizes taro and moringa leaves, which are known to have high nutritional content. This training involved the local community in the noodle-making process, which includes the stages of preparing ingredients, processing the dough, forming noodles, and boiling. The main ingredients used are steamed and mashed taro, blended moringa leaves, as well as wheat flour, eggs, vegetable oil, and simple spices. The noodle-making process is carried out practically and simply, so that people can easily practice it at home. The final result of this training is taro and moringa leaf noodles that can be modified into various dishes. This training is expected to be able to increase the economic potential of the village by developing local products that are highly nutritious and have sales value. The superfood keke noodle product is expected to be an alternative healthy food that can compete in the market, while improving the welfare of the people of Tumuk Manggis Village. This collaboration also emphasizes the importance of utilizing abundant local food ingredients as an innovation for superior products. This activity ended with gratitude to the Tumuk Manggis Village government for its support and collaboration in implementing this training.